2008
DOI: 10.1007/s00438-008-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic expression of twelve rice PR1 family genes in response to pathogen infection, wounding, and defense-related signal compounds (121/180)

Abstract: Pathogenesis-related (PR) proteins have been used as markers of plant defense responses, and are classiWed into 17 families. However, precise information on the majority members in speciWc PR families is still limited. We were interested in the individual characteristics of rice PR1 family genes, and selected 12 putatively active genes using rice genome databases for expressed genes. All were upregulated upon compatible and/or incompatible rice-blast fungus interactions; three were upregulated in the early inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(191 citation statements)
references
References 30 publications
10
179
0
2
Order By: Relevance
“…Exogenous JA and ET supply on the rice shoots resulted in a strong induced defense in the systemic tissue, exemplified by the strong up-regulation of PR genes OsPR1a and OsPR1b, which are generally seen as SAR marker genes. This observation is in line with their local responsiveness to many endogenous and exogenous signals (Jwa et al, 2006;Mitsuhara et al, 2008), but their systemic up-regulation in rice roots upon foliar JA/ET supply has never been demonstrated before. Previously, it was reported that OsPR1b is locally up-regulated by JA but downregulated by the ET precursor 1-aminocyclopropane-1-carboxylic acid (Agrawal et al, 2000;Mei et al, 2006;Mitsuhara et al, 2008), while we demonstrate an upregulation of this gene in systemic tissues upon ethephon treatment.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Exogenous JA and ET supply on the rice shoots resulted in a strong induced defense in the systemic tissue, exemplified by the strong up-regulation of PR genes OsPR1a and OsPR1b, which are generally seen as SAR marker genes. This observation is in line with their local responsiveness to many endogenous and exogenous signals (Jwa et al, 2006;Mitsuhara et al, 2008), but their systemic up-regulation in rice roots upon foliar JA/ET supply has never been demonstrated before. Previously, it was reported that OsPR1b is locally up-regulated by JA but downregulated by the ET precursor 1-aminocyclopropane-1-carboxylic acid (Agrawal et al, 2000;Mei et al, 2006;Mitsuhara et al, 2008), while we demonstrate an upregulation of this gene in systemic tissues upon ethephon treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Only mRNA levels of pathogenesis-related gene OsPR1a and OsWRKY45, known to be a key regulator of the SA signaling pathway and involved in BTH-induced resistance to Magnaporthe grisea (Shimono et al, 2007), were higher in comparison with basal levels. OsPR1b, on the other hand, a gene that is commonly seen as SA inducible (Agrawal et al, 2000;Mitsuhara et al, 2008) and therefore generally accepted as a SAR marker gene, is not induced in systemic root tissue upon foliar Nahar et al application of BTH. In contrast, our data show that foliar supply of MeJA or ethephon results in a systemic up-regulation of OsPR1b, which is strongest upon MeJA treatment (factor = 20.9) and 9.7-fold upon ethephon application.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analyses of 50 large gene families in the Arabidopsis genome revealed a large variation in apparent tandem duplication rates among families (Cannon et al, 2004). Interestingly, the majority of the most rapidly evolving families were associated with pathogen defense and included NB-LRR genes, the Major Latex Protein family (related to the pathogeninducible PR10 proteins; Osmark et al, 1998), the Germin family (Membre et al, 2000), subtilisin-like Ser proteases (Jorda and Vera, 2000), and the pathogenesis-related PR1 family (Mitsuhara et al, 2008). These findings suggest that the apparent differences in duplication rates (and hence unequal crossover rates) may be partly explained by pathogen-mediated selection.…”
Section: Discussionmentioning
confidence: 99%
“…PR genes are generally induced after pathogen infection or other stresses, and are widely used as markers for cell death and defense responses such as systemic acquired resistance (van Loon et al, 2006). Pathogen and salicylicacid-responsive genes PR1a and PR1b (Mitsuhara et al, 2008) as well as the cell-death-related marker gene PR10 (Kim et al, 2011) were all significantly up-regulated in noninoculated leaves of cslf6 mutants (Fig. 8, C-E).…”
Section: Mutations In Cslf6 Affect the Mechanical Properties Of The Cmentioning
confidence: 96%